2012
DOI: 10.1021/es301110e
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Availability for Future Automotive Technologies

Abstract: Platinum is an excellent catalyst, can be used at high temperatures, and is stable in many aggressive chemical environments. Consequently, platinum is used in many current industrial applications, notably automotive catalytic converters, and prospective vehicle fuel cells are expected to rely upon it. Between 2005 and 2010, the automotive industry used approximately 40% of mined platinum. Future automotive industry growth and automotive sales shifts toward new technologies could significantly alter platinum de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 30 publications
1
82
0
Order By: Relevance
“…The demand of the petroleum industry depends on the build-up of production capacities, whereas the demand of the electronic industry is linked to the demand for consumer goods. In the years following the August 2007 financial crisis, the increase in total demand was largely met by an increase in recycling [21,22].…”
Section: Use and Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand of the petroleum industry depends on the build-up of production capacities, whereas the demand of the electronic industry is linked to the demand for consumer goods. In the years following the August 2007 financial crisis, the increase in total demand was largely met by an increase in recycling [21,22].…”
Section: Use and Demandmentioning
confidence: 99%
“…Pd superseded Pt in three-way catalysts in recent years and is gradually taking over the market share of Pt in the catalytic converter market. Pd is superseded by other materials in the case of electric consumer goods [21].…”
Section: Use and Demandmentioning
confidence: 99%
“…Important examples have been: neodymium and dysprosium for permanent magnets used in wind turbines and electric vehicles [22][23][24][25]; platinum group metals (PGMs) with particular reference to fuel cell technology [23,[26][27][28][29][30][31]; photo-active materials for thin-film solar cells (cadmium, tellurium, selenium, gallium, indium) [32][33][34][35][36][37][38]; lithium for batteries in electric vehicles [39][40][41][42][43]; rare earth elements (REE) (rare earth elements typically include 17 elements, scandium, yttrium, and the lanthanide series. In the case of this study, the REE of interest are neodymium, dysprosium and yttrium.…”
Section: Critical Minerals and Unconventional Resourcesmentioning
confidence: 99%
“…These studies have in general identified that there could be high increases in demand, but that the limitations on supply are likely to be short-term constraints. With regard to the specific metals, PGM studies have had mixed conclusions with some arguing that supply issues are unlikely to be problematic [27,30], while others have indicated that demand will outstrip supply [28,31], and that in the short term, some challenges with electricity shortages in South Africa have the potential for disruption to supply [31]. In the case of lithium, most studies have indicated that the resources are sufficient for potential future scenarios [39,43]; however, there were some concerns about the physical potential for industry to expand at the required rate [41].…”
Section: Critical Minerals and Unconventional Resourcesmentioning
confidence: 99%
See 1 more Smart Citation